Murder in the ball park - Goldsborough, Robert (MysteriousPress.com/Open Road Integrated Media, 2014)
"Archie Goodwin and Saul Panzer have ventured into the wilds of northern Manhattan to watch the Giants take on the Dodgers at the Polo Grounds. Panzer spies state senator Orson Milbank, a silver-haired scoundrel with enemies in every corner of upstate New York, sitting in the box seats. In the fourth inning, a monstrous line drive brings every fan in the grandstand to his feet -- every fan save for one silver-haired senator, who has been shot dead by a sniper in the upper deck. Archie's employer, Nero Wolfe, has no interest in investigating the stadium slaying, but Archie is swayed by the senator's suspiciously lovely widow. Her husband was hip-deep in corruption, and sorting out who killed him will be a task far less pleasant than an afternoon at the ball park."__p. [4] of cover.